The emergence of China in international academic management research: A nuanced analysis following the new f²-methodology - Fassin, Yves (Malaysian Journal of Library and Information Science, 2021)
In a few decades, China has made a huge rise in science, exemplified with an impressive expansion of academic publications. The management field has traditionally been dominated by the US universities and Anglo-Saxon researchers. The objective of the present study is to analyze through the application of a new bibliometric methodology whether the progress of Chinese universities in academic management research is in line with China’s overall progress in science. The classic analysis of volume productivity and citation count is complemented with the recent f²-methodology. It is based on a more fine-grained classification of publications into categories of citations, focusing on the 10%-percentile and the h-core. The methodology is applied here at a country level and at the level of the university, for all publications and for those of the last 5 years. The results confirm the rise of academic publications by Chinese management scholars, but the analysis of publication outlets and the international collaborations nuance this progress. The US dominance in academic management research is maintained; despite a decline in relative terms, the US publication volume and the higher citations remain in absolute terms. This application of the f²-methodology with weighted factors in function of impact brings nuances to first level bibliometric analyses based on volume productivity or on total citations. This nuanced analysis results in fairer assessments and more equitable rankings. The application of the compound F²-index illustrates the dynamics in bibliometrics.